Art as a vehicle for social change: The harlem renaissance - Azmi, M.N.L.; Chelihi, R.K.; Nouri, K. (2018)
The black gatherings particularly in Harlem, constituting a community with its peculiarities, thanks to the effective contributions of intellectuals and artists through a new movement called the Harlem Renaissance urging the Blacks to struggle peacefully to gain more rights. For about thirty years, African Americans used arts in their battle to dispel common stereotypes. The origins of the movement were articulated in the philosophies of some prominent figures like W. E. Dubois and Allen Locke. The black community is a reality within the U.S.A, no one can deny its rights and this thanks to the struggles it has led, and to artistic contribution which has made the USA a nation with specificities, different from white man's country of origin. It sheds light also on the work of Toni Morrison's Song of Solomon to stress the continuing heritage of the Harlem. A descriptive analytical analysis based on Cultural pluralism and Americanism concepts of Franz Boas' theories of race and culture (1930) is used in this research. The aim of the study is to show the role the elites can play to improve their communities' status and the importance of art in shaping identities and giving insights for a better future. The Harlem Renaissance established the careers of many important African American writers, artists and thinkers who were influential for decades. It brought forth a body of creative cultural work that have become classics in African American and American culture. It created an ongoing interest in African American culture that continues up to this day.